Tuning rules for energy-based control methods for mechanical systems - Chan Zheng, Carmen 1989- (2023)
Modern applications demand faster, more sophisticated, more precise, and more powerful robotic systems that can handle harsh environments. Simultaneously, this trend also creates new challenges for modeling and control design as the nonlinear phenomena are no longer negligible. Despite the popularity of linear control techniques in the industry -due to their availability- they are not suitable to deal with the demands as nonlinear dynamics are becoming richer. In fact, disregarding these behaviors during the modeling and control design stages may lead to poor performance or instability. For example, the effect of "hard linearities" -such as Coulomb friction, dead-zones, saturation, asymmetry of the motors, backslash, or hysteresis- cannot be analyzed with linear techniques, and these phenomena may lead to steady-state errors. Regardless of the clear advantages of the nonlinear control schemes - e.g., stability guarantees are inherent in these methodologies - in comparison with their linear counterpart, there is still an evident gap between practitioners and theorists. The implementation of the nonlinear schemes is hampered in practice due to the lack of tuning guidelines in the literature as the vast majority of the methodologies are devoted to designing controllers to achieve the performance in terms of stability, disregarding other performance indices. Nonetheless, in several applications, it is crucial to prescribe per- formance to solve a task at hand, e.g., high-precision applications such as those found in medical, aerospace, and other industries. Hence, this thesis provides a comprehensive set of tuning rules for a class of nonlinear control schemes, namely, passivity-based control (PBC) approaches. These schemes aim to render the closed loop stable via two steps: i) the energy shaping (or power shaping) process and ii) the damping injection step. For the former step, the energy shaping (or power shaping) process assigns the desired...